Evaluation of the behavior and ultimate capacity of unbonded monostrand-anchorage systems under concentric and eccentric inelastic cyclic loading - Bedriñana L.A. (2018)
The financial support of the Peruvian National Council of Science, Technology, and Technological Innovation (CONCYTEC/CIENCIACTIVA) for the doctoral studies of the first author is acknowledged. In addition, the authors would like to thank Sumitomo Steel Wire Corp. (SEI-SSW) for the generous donation of strands and anchorages for this test. The authors acknowledge the technical support of Mr. Masato Yamada and Mr. Katsuhito Oshima from SEI-SSW during the course of this research. Authors would like to thank the support of Tsuyoshi Takahashi, graduate student at Kyoto University, during the testing. All opinions, findings, and conclusions stated in this paper are those of the authors and do not necessarily reflect the views of the supporting institutions.